# Prove $\operatorname{rank}A^TA=\operatorname{rank}A$ for any $A\in M_{m \times n}$

How can I prove $$\operatorname{rank}A^TA=\operatorname{rank}A$$ for any $$A\in M_{m \times n}$$?

This is an exercise in my textbook associated with orthogonal projections and Gram-Schmidt process, but I am unsure how they are relevant.

• Obligatory remark: This holds when $A\in\mathbb R^{m\times n}$, but not (for instance) when $A\in\mathbb C^{m\times n}$. Apr 3, 2013 at 4:31
• See this counter-example for the case where $A\in\mathbb C^{m\times n}$. Jan 13, 2016 at 22:43
• Or $A^T=(1~~\mathbf i)$. Apr 27, 2016 at 14:52
• The conclusion also fails for fields of nonzero characteristic (finite fields in particular). See the comment by @Member below on the Accepted Answer, identifying the crucial step that $(Ax)^T(Ax) = 0$ implies $Ax=0$. Jun 8, 2017 at 17:44

Let $\mathbf{x} \in N(A)$ where $N(A)$ is the null space of $A$.

So, \begin{align} A\mathbf{x} &=\mathbf{0} \\\implies A^TA\mathbf{x} &=\mathbf{0} \\\implies \mathbf{x} &\in N(A^TA) \end{align} Hence $N(A) \subseteq N(A^TA)$.

Again let $\mathbf{x} \in N(A^TA)$

So, \begin{align} A^TA\mathbf{x} &=\mathbf{0} \\\implies \mathbf{x}^TA^TA\mathbf{x} &=\mathbf{0} \\\implies (A\mathbf{x})^T(A\mathbf{x})&=\mathbf{0} \\\implies A\mathbf{x}&=\mathbf{0}\\\implies \mathbf{x} &\in N(A) \end{align} Hence $N(A^TA) \subseteq N(A)$.

Therefore \begin{align} N(A^TA) &= N(A)\\ \implies \dim(N(A^TA)) &= \dim(N(A))\\ \implies \text{rank}(A^TA) &= \text{rank}(A)\end{align}

• How does $(Ax)^T (Ax)=0$ implys $Ax=0$?
– user268307
Dec 20, 2015 at 21:56
• @AnuragJain note that for any vector $y$, $y^Ty = \|y\|^2$. Also, note that this question was asked two years ago, so you're unlikely to catch the attention of the original asker. Dec 20, 2015 at 21:58
• The last step $\dim(N(A^TA)) = \dim(N(A)) \implies \text{rank}(A^TA) = \text{rank}(A)$ is due to rank-nullity theorem. Apr 2, 2018 at 17:57
• Hi @A.D how it will work for $A^*$ , i mean how to show that $rank(A)=rank(AA^*)=rank(A^*A)$, is it the same? Dec 3, 2020 at 16:36
• @user726608 Same manner Sep 28, 2021 at 12:22

Let $r$ be the rank of $A \in \mathbb{R}^{m \times n}$. We then have the SVD of $A$ as $$A_{m \times n} = U_{m \times r} \Sigma_{r \times r} V^T_{r \times n}$$ This gives $A^TA$ as $$A^TA = V_{n \times r} \Sigma_{r \times r}^2 V^T_{r \times n}$$ which is nothing but the SVD of $A^TA$. From this it is clear that $A^TA$ also has rank $r$. In fact the singular values of $A^TA$ are nothing but the square of the singular values of $A$.

• Note that from Strang's textbook, it actually use the fact that, there're $r$ non-zero eigenvalues of $A^TA$ i.e. $rank(A^TA)=rank(A)$, to decide the size of $\Sigma_{r \times r}$ and prove the SVD. To avoid circular argument here it would require a different SVD proof. Jan 6, 2021 at 12:03

Since elementary operations do not change the rank of a matrix we have $$\text{rank}(A^TA) = \text{rank}(E^TA^TAE)$$, where $$E$$ is a multiplication of several elementary operations which make $$AE = [A_1, A_2]$$, where $$A_1$$ is a column full rank matrix with $$\text{rank}(A_1) = \text{rank}(A)$$.

Thus we can find a matrix $$P$$ such that $$A_1P= A_2$$ and $$AE = [A_1, A_1P] = A_1[I, P]$$.

Thus $$\text{rank}(E^TA^TAE) = \text{rank}(A_1[I, P])^T(A_1[I, P])$$. In this equation, the matrices are all of full rank and the rank equals $$\text{rank}(A)$$, so on a real space $$\text{rank}(A^TA) = \text{rank}(A)$$, completing the proof.

• I cannot decipher what is said here, but it must be wrong since it never uses that the matrices are over $\Bbb R$ (or more generally an ordered field) rather than for instance over $\Bbb C$ where the result is not true. Apr 27, 2016 at 14:38
• The last theorem actually implicitly uses they are over real space. Thank you for pointing that out. I have added that prerequisite into my answer. Apr 30, 2016 at 4:47
• An alternative simple way to see it: Matrix $A^T$ may be reduced to its reduced row-echelon form, $R$, by $PA^T=R$, where $P$ is the product of a sequence of elementary matrices. So, $A^T=P^{-1}R$ and hence $$\mathrm{rank}(A^TA)=\mathrm{rank}(P^{-1}RR^T(P^{-1})^T)=\mathrm{rank}(RR^T).$$ The result then follows easily from this, since clearly $\mathrm{rank}(RR^T)=\mathrm{rank}(R)=\mathrm{rank}(A).$ Jan 14, 2017 at 2:07
• @syeh_106 Why is it that $\operatorname{rank}(RR^T)=\operatorname{rank}(R)$? I'm sorry if this is too basic. Aug 17, 2020 at 19:08
• @JPYamamoto If $R^T$ is full column rank, this is clearly true: $RR^Tx=0 \Rightarrow x^TRR^Tx=\Vert R^Tx\Vert^2=0 \Rightarrow R^Tx = 0 \Rightarrow x = 0$, i.e. $RR^T$ is still full column rank. Otherwise, $R^T= [R_1^T\, 0]$, where $R_1^T$ is full column rank, and it's easily verified that $\mathrm{rank}(RR^T)=\mathrm{rank}(R_1R_1^T)=\mathrm{rank}(R_1)=\mathrm{rank}(R).$ Aug 19, 2020 at 4:33